Analisis Faktor-Faktor Produksi Perikanan Di Kota Kupang (Studi Kasus: Budidaya Ikan Air Tawar Di Kecamatan Kota Raja Dan Kecamatan Alak) - Rayzcha Monicha Immerghanzhia Hotty; Chaterina Agusta Paulus; Edi Rusdiyanto (Jurnal Perikanan Unram, 2024)
The study focuses on the analysis of the production factors that influence the sustainability of fish farming in the Raja District and Kupang District. This research aims to provide knowledge about the efficiency of fishing production and sustainability status. The research methods used are descriptive and analytical, involving the study of literature, observation, and statistical testing to analyse the relationship between the factors of production and sustainability of fish Lele (Clarias sp) and Nila (Oreochromis Niloticus). The analytical methods used include the Cobb-Douglas Function using SPSS version 25. The analysis involved testing classical assumptions to determine data distribution, testing regression models to understand the influence of production factors on fish production, and then analysing the sustainability of freshwater fish farming, looking at economic, social, and environmental aspects. The findings show that the regression model used shows a high degree of confidence in explaining the relationship between and the influence of independent variables (X1,X2,X3,X4,X5) on the dependent variable (Y). Based on research conducted on the sustainability of freshwater fish farming in Raja City and Kupang Alak City districts, it can be concluded that production factor analysis provide useful insights for stakeholders, policymakers, and researchers. These studies have shown that the efficiency of production factors can have a significant impact on various aspects of sustainability, including the social and environmental dimensions.